Long-term production effects of clinical cryptosporidiosis in neonatal calves. Issue 5 (May 2020) - Shaw, Hannah J.; Innes, Elisabeth A.; Morrison, Liam J.; Katzer, Frank; Wells, Beth
Graphical abstract: Highlights: Cryptosporidium parvum is a major cause of enteric disease in neonatal calves. Clinically severe cryptosporidiosis in neonatal calves significantly reduces weight gain. The impact of reduced weight gain in calves is seen over a 6 month period. Abstract: Cryptosporidiosis can have a devastating effect in neonatal calves, resulting in diarrhoea, dehydration and, in severe cases, death of the animal. The disease is caused by Cryptosporidium spp. and is one of the most common causes of calf enteritis in the UK. The parasite is very difficult to remove from the farm, as the oocysts have a tough outer wall which enables the parasite to survive for several months in moist temperate environmental conditions and it is difficult to kill oocysts with common disinfectants used on a farm. If appropriate management practises are applied, the disease is usually self-limiting and most calves will recover. It has been shown, in studies with children and in lambs, that severe clinical cryptosporidiosis can result in long-term growth and cognitive impairment compared with individuals with no obvious signs of the disease. This study measured the long-term growth rate of beef calves on farm by comparing groups of animals that had suffered differing degrees of clinical severity of cryptosporidiosis as neonates. A group of 27 beef calves were enrolled in the study and monitored from birth to 6 months of age. The calves were scored for severity of cryptosporidiosis and weighed at regular intervals. The average difference in weight gain, at 6 months, between a group of calves that had severe cryptosporidiosis as neonates and a group of calves with no clinical signs of infection was 34 kg. Those calves that had experienced severe cryptosporidiosis as neonates showed a significantly reduced live weight gain compared with those calves showing no clinical signs of infection ( P = 0.034). Therefore, the impact of severe cryptosporidiosis in neonatal calves has longer term effects on weight gain and production efficiency, resulting in the parasite having a greater impact on cattle production than previously thought.